A Mixed‐Method Approach to Evaluate a Pharmacist Intervention for Veterans With Hypertension. Issue 2 (February 2014) - Parker, Christopher P.; Cunningham, Cassie L.; Carter, Barry L.; Vander Weg, Mark W.; Richardson, Kelly K.; Rosenthal, Gary E.
<x xml:space="preserve">Abstract</x> This paper examines blood pressure (BP) control after 6 months of an intensive pharmacist‐managed intervention in a mixed‐methods randomized controlled trial conducted at the Iowa City Veteran Affairs Health Care System and two community‐based outreach clinics. Patients received the pharmacist intervention for the first 6 months. The study coordinator conducted a summative evaluation with 37 patients 18 to 24 months following the initial 6‐month intervention period. BP was significantly reduced in diabetic patients following an intensive pharmacist intervention (−8.0/−4.0±14.4/9.1 mm Hg systolic/diastolic, P<.001 and P=.001, respectively). BP was reduced even more in nondiabetic patients (−14.0/−5.0±1.9/10.0 mm Hg, P<.001). Medication adherence significantly improved from baseline to 6 months (P=.017). BPs were significantly lower at 6 months following an intensive pharmacist intervention. Patients also expressed a high level of satisfaction with and preference for co‐management of their hypertension, as well as other chronic diseases.